Concomitant Kommerell diverticulectomy, carotid-subclavian bypass, and modified ravitch pectus excavatum repair via sternotomy - Carlo R Bartoli; Shiv Patel; Victor Mallory; Deborah Miller (Journal of Cardiothoracic Surgery)
Abstract Congenital heart disease may present with pectus excavatum. Concomitant and staged repair are described, but the optimal approach is controversial. We report a 17-year-old male with left aortic arch, aberrant right subclavian artery, and Kommerell diverticulum who presented with long standing swallowing difficulties, prandial nausea, and pectus excavatum with cosmetic concerns. Kommerell diverticulectomy, carotid-subclavian bypass, and modified Ravitch pectus excavatum repair were performed without complication. Concomitant congenital heart surgery and pectus excavatum repair may be successfully performed in a single operation via sternotomy. Incidence, operative approaches, and complications of concomitant versus staged correction of congenital heart disease and pectus excavatum are briefly reviewed.